2020
DOI: 10.3389/fgene.2020.00641
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils, Crucial, or Harmful Immune Cells Involved in Coronavirus Infection: A Bioinformatics Study

Abstract: The latest member of the Coronaviridae family, called SARS-CoV-2, causes the Coronavirus Disease 2019 (COVID-19). The disease has caused a pandemic and is threatening global health. Similar to SARS-CoV, this new virus can potentially infect lower respiratory tract cells and can go on to cause severe acute respiratory tract syndrome, followed by pneumonia and even death in many nations. The molecular mechanism of the disease has not yet been evaluated until now. We analyzed the GSE1739 microarray dataset includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 28 publications
(26 reference statements)
3
65
0
2
Order By: Relevance
“…In humans, neutrophils are the most abundant type of peripheral WBC with prominent functions in the acute inflammatory response by migrating toward injured tissues in response to chemoattractant signals such as interleukin (IL-) 8 [ 29 ]. Neutrophils are now considered one of the most important immune cells in defending the airway epithelium against the SARS-CoV-2 infection by locally stimulating the production of IL-1 beta, IL-6, tumor necrosis factor-alpha (TNF-alpha), and reactive oxygen species (ROS) [ 30 ]. Paradoxically, neutrophil hyperactivation and recruitment intensify the acute inflammatory response and worsen epithelial tissue damage thus leading to disease progression [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, neutrophils are the most abundant type of peripheral WBC with prominent functions in the acute inflammatory response by migrating toward injured tissues in response to chemoattractant signals such as interleukin (IL-) 8 [ 29 ]. Neutrophils are now considered one of the most important immune cells in defending the airway epithelium against the SARS-CoV-2 infection by locally stimulating the production of IL-1 beta, IL-6, tumor necrosis factor-alpha (TNF-alpha), and reactive oxygen species (ROS) [ 30 ]. Paradoxically, neutrophil hyperactivation and recruitment intensify the acute inflammatory response and worsen epithelial tissue damage thus leading to disease progression [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are now considered one of the most important immune cells in defending the airway epithelium against the SARS-CoV-2 infection by locally stimulating the production of IL-1 beta, IL-6, tumor necrosis factor-alpha (TNF-alpha), and reactive oxygen species (ROS) [ 30 ]. Paradoxically, neutrophil hyperactivation and recruitment intensify the acute inflammatory response and worsen epithelial tissue damage thus leading to disease progression [ 30 , 31 ]. On the contrary, lymphocytes are very important leukocytes in charge of mediating immune tolerance to self-antigens, activation of pathogen-specific adaptive immunity, and, last but not less important, orchestration of immunomodulatory mechanisms [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of neutrophils in severe COVID-19 has received immense attention. Specifically, a microarray-based study of SARS-CoV-2 infected a peripheral blood mononuclear cell (PMBC) and single cell analysis of epithelial and immune cells in COVID-19 patients revealed that the neutrophil markers were overexpressed, suggesting that the patients were under neutrophilia [9,10]. Furthermore, a meta-analysis based on gene network constructed from the published datasets derived several neutrophil-enriched genes [11].…”
Section: Functional Characteristics Distinguish the Severe Covid-19 Gmentioning
confidence: 99%
“…Activation and degranulation of these cells in the microenvironment of infected cells can damage the host tissue and worsen the disease outcome. The neutrophils, via the induction of pro-inflammatory cytokines, as well as ROS production, could worsen the disease manifestation [64] . It is suggested that severe host response in the infected patients with COVID-19 is due to improper activation of leukocytes such as neutrophils in peripheral blood.…”
Section: Immune Responsementioning
confidence: 99%